Agreements Between the Ayyubid state and the Zaidi sect In Yemen (569 – 626 AH/1173 – 1229AD): Analytical historical study - Hemin Rashid Khorsheed; Arsn Musa Rashid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The research shows the friendly relations of the Ayyubid state with the Zaidi sect in Yemen during the era of the presence of the Ayyubids in it, and shows their friendly relations during fifty-seven years. Notables and supervision in the Zaidi sect, but they joined the Ayyubids, and among the Kurdish leaders who were from the Ayyubid army, but they joined the Zaidi imam, then the research sheds light on the peaceful agreements that took place between the Ayyubid state and the Zaidi sect, explaining the contents of each of them, and in the end the research explains the position of the Ayyubid state on the doctrine Al-Zaidi throughout the period of the presence of the Ayyubids in Yemen.